Lithium in the Environmental Geopolitics of the United States: The Tension with China for the Chilean Case - Estenssoro-Saavedra, J (UNIV ALBERTO HURTADO, 2023)
This essay argues that access to lithium mineral sources is acquiring a strategic and national security nature for the United States, in the context of climate change and the urgent need to replace the global "fossil" energy grid. This situation, together with the rivalry that the United States has with China, would lead to renewed US interference in Latin American countries with large exploitations and reserves of this resource, as is the case of Chile. The American superpower has begun to exert pressure on the country s government, authorities and public opinion, aiming to expel or significantly reduce the growing importance of Chinese capital in the exploitation of this resource. A pressure that would increase as the rivalry with China continues to increase.